The Effect of Covid-19 Pandemic on Teachers’ Outdoor Learning - Danai, Rudra Prasad (AMC Journal, 2022)
"The Effect of Covid-19 Pandemic on Teachers Outdoor Learning" is quantitative research that studies how the teachers of Dhading are exploring their alternatives to continue to learn. The objectives of this research are to explore how teachers are continuing their learning during the long lockdown period when they are formally detached from face-to-face teaching and learning and what alternatives of schooling for the children the teachers are exploring during the lockdown. This research follows the online survey design with a positivist worldview of the facts. This research follows a simple random sampling method for choosing the population who are the teachers teaching in Dhading. This research employed close-ended questions asked online and the data are analyzed by using SPSS. The researcher found that theCOVID-19 and the lockdown, despite its direct effect on regular teaching and learning, has not fully deteriorated the teachers’ learning but they have made innovations in learning methods and their horizons. This study also proves that the teachers have got more benefits from their colleagues and professional unions, and they have got a good opportunity of learning information communication technology (ICT), new pedagogy, and the contents of their subject matters. This research suggests that the online prospect is the best one for students and teachers to get access over the big horizon of teaching and learning. Teachers have understood it as an opportunity for innovation. It is concluded that the COVID-19 lockdown though appeared to halt their teaching and learning routine, has not made a blockade on their learning.